Tinjauan Debit Andalan Untuk Irigasi Di Kecamatan Sungai Tabuk Kabupaten Banjar - Fakhrurrazi Fakhrurrazi; Herliyani Farial Agoes; Desy Anggeriyani (Jurnal Teknik Sipil, 2018)
Adequate water availability in irrigation systems is an important factor in the success of irrigation agriculture, including Sungai Tabuk irrigation system which land is planted with rice paddy, fields rice paddy and crops. The availability of water in Kecamatan Tabuk River was calculated by dependable flow analysis using flow data from Mock method calculation. The model of rainfall-flow relationship with the monthly interval used was Mock Method, and 80% dependable flow was used to calculate the availability of the irrigation water. Based on the rainfall and evapotranspiration data (Mock method) in irrigation system of Sungai Tabuk area, the average flow per year of 5.758 m3 / sec obtained. With the highest flow occurred in March of 9.405m3 / sec and the lowest flow was in September at 1.616 m3 / sec. The 80% dependable flow was an average of 3.504 m3 / sec with the highest 80% of the highest dependable flow recorded in February of 7.37 m3 / sec and the lowest flow was in October which 80% flow was 0.24 m3 / sec. The calculation of irrigation water needed was based on KP-01. The calculation results showed that the average water demand was 2.690 m3 / sec with the beginning of planting on December I by using ordinary rice-ordinary rice planting pattern; while the average water demand for crops was 0.029 m3 / sec. From the analysis, the availability of irrigation water of Sungai Tabuk (average value of 3,504 m3 / sec) can fulfil the irrigation water requirement (average value of 2,690 + 0,029 = 2,719 m3 / second).